Customer satisfaction, behavioural and pay more intentions: a study on Indian Dhabas (roadside full-service restaurants). (14th March 2023) - Kumar, Pankaj; Ahlawat, Pardeep K.; Kumar, Parveen; Kumar, Jitender
The present study examines the foremost antecedents of customer satisfaction, behavioural and pay more intentions in the setting of Indian Dhabas (roadside full-service restaurants) located on the National highway, Haryana, India. Using the convenience sampling technique, 236 self-administrated survey questionnaires were collected (207 considered usable) from the customers who had experienced dining at Indian Dhabas, and were tested by performing partial least squares-structural equation modelling (PLS-SEM). The results confirmed that customer satisfaction is significantly influenced by the atmospheric quality, service quality, and food quality of Dhabas, and customer satisfaction significantly influences trust in a positive manner. Remarkably, the impact of customer satisfaction on behavioural intentions was more significant than trust. Further, trust and behavioural intentions have significant positive influences on pay more intentions, while the effect of customer satisfaction on pay more intention is positive, but it is insignificant. Essentially, the present study attempts to provide valuable insights into customer satisfaction and consumer behavioural and pay more intentions to Dhabas' (roadside full-service restaurants) owners and managers to build long-term relationships with Dhabas' customers.